2020
DOI: 10.1609/aaai.v34i03.5629
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Engineering Human/Agent Teaming Systems

Abstract: The increasing capabilities of autonomous systems offer the potential for more effective teaming with humans. Effective human/agent teaming is facilitated by a mutual understanding of the team objective and how that objective is decomposed into team roles. This paper presents a framework for engineering human/agent teams that delineates the key human/agent teaming components, using TDF-T diagrams to design the agents/teams and then present contextualised team cognition to the human team members at runtime. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…TDF [15,16] is the successor to Prometheus [25], a mature and popular AOSE methodology. A pilot study has shown that TDF significantly improves comprehension of behaviour models, compared to UML [18].…”
Section: Tdf and Sarlmentioning
confidence: 99%
See 1 more Smart Citation
“…TDF [15,16] is the successor to Prometheus [25], a mature and popular AOSE methodology. A pilot study has shown that TDF significantly improves comprehension of behaviour models, compared to UML [18].…”
Section: Tdf and Sarlmentioning
confidence: 99%
“…Most agent design methodologies support the translation from design to implementation. The detailed agent diagrams in TDF are readily translated to implementation constructs in agent implementation languages such as JACK [17] and SARL [15].…”
Section: System Story Mappings and Traceabilitymentioning
confidence: 99%
“…For instance, BO-MUSE employs Bayesian methods to optimize the experimental design involving human-AI teams (Gupta et al 2023). Evertsz and Thangarajah employ TDF-T diagrams to engineer humanagent teams and provide context-specific team cognition to human team members during the runtime of the StarCraft strategy game (Evertsz and Thangarajah 2020).…”
Section: Introductionmentioning
confidence: 99%